2019
DOI: 10.3390/v11121152
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia Lake Virus Does Not Hemagglutinate Avian and Piscine Erythrocytes and NH4Cl Does Not Inhibit Viral Replication In Vitro

Abstract: Tilapia lake virus (TiLV) is a negative-sense single-stranded RNA (-ssRNA) icosahedral virus classified to be the only member in the family Amnoonviridae. Although TiLV segment-1 shares homology with the influenza C virus PB1 and has four conserved motifs similar to influenza A, B, and C polymerases, it is unknown whether there are other properties shared between TiLV and orthomyxovirus. In the present study, we wanted to determine whether TiLV agglutinated avian and piscine erythrocytes, and whether its repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
3
7
0
Order By: Relevance
“…In the penetration-inhibition assay, we further studied the effect of Aβ 1–42 on the EV-A71 RNA level at 1 h post-virus attachment (MOI = 2.5). Figure 3 c shows that consistent with NH 4 Cl treatment [ 23 ], Aβ 1–42 efficiently downregulated the level of VP1 RNA after EV-A71 attachment in all three cell lines.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In the penetration-inhibition assay, we further studied the effect of Aβ 1–42 on the EV-A71 RNA level at 1 h post-virus attachment (MOI = 2.5). Figure 3 c shows that consistent with NH 4 Cl treatment [ 23 ], Aβ 1–42 efficiently downregulated the level of VP1 RNA after EV-A71 attachment in all three cell lines.…”
Section: Resultssupporting
confidence: 58%
“…In the penetration-inhibition assay, we further studied the effect of Aβ 1-42 on the EV-A71 RNA level at 1 h post-virus attachment (MOI = 2.5). Figure 3c shows that consistent with NH 4 Cl treatment [23], Aβ 1-42 efficiently downregulated the level of VP1 RNA after EV-A71 attachment in all three cell lines. Taken together, these results demonstrated that Aβ 1-42 primarily targeted EV-A71 attachment, internalization, and uncoating stage to inhibit virus replication.…”
Section: Aβ 1-42 Targeted the Early Stage Of The Ev-a71 Life Cyclesupporting
confidence: 61%
“…In addition to the liver and brain, positive hybridization signals were also detected in the anterior kidneys, gills, gastrointestinal tract and spleen, as well as in the connective tissues of infected fish (Bacharach et al., 2016; Jaemwimol et al., 2018; Jansen et al., 2019). A recent study demonstrated that a lysosomotropic agent had no effect on TiLV replication, suggesting that TiLV can replicate without acidic pH in contrast to other orthomyxoviruses (Chengula, Mutoloki, Evensen, & Munang’andu, 2019).…”
Section: Tilv Pathogenesismentioning
confidence: 99%
“…Other serological applications, such as haemagglutinin (HA) test, were carried out for TiLV but the results demonstrated that TiLV did not agglutinate turkey ( Meleagris gallopavo ), Atlantic salmon ( Salmo salar L ) and Nile tilapia ( O. niloticus ) red blood cells. Interestingly, this suggests that TiLV likely uses other mechanisms to bind and enter into fish cells (Chengula et al., 2019), and such mechanisms need to be further investigated.…”
Section: Diagnosis Of Tilvmentioning
confidence: 99%
“…Despite being an orthomyxo-like virus, the mode of TiLV entry into the cells is largely unknown. Differences from other orthomyxoviruses, including the prototypic influenza viruses and the infectious salmon anemia virus (ISAV), have been suggested, as TiLV does not hemagglutinate erythrocytes, and as ammonium chloride does not inhibit its replication ( Chengula et al, 2019 ). Here, we employed different inhibitory treatments to dissect the cellular requirements for TiLV entry and replication in tilapia cells.…”
Section: Introductionmentioning
confidence: 99%